Method for hidden marking of transparent polypropylene film - A. A. Nikolaev; A. P. Kondratov (Тонкие химические технологии)
Objectives. To quantitatively describe the thermochromic properties of films of isotactic polypropylene, a large-tonnage polymer widely used in the production of flexible packaging for goods and foodstuffs, as well as substantiate the possibility of covert labeling of transparent packaging.Methods. Differential scanning calorimetry, polarization photometry, infrared Fourier spectrometry, gravimetry, temperature control, physical and mechanical strength testing.Results. The identified thermochromic effect of dichroism in polarized light on industrial samples of transparent biaxially oriented film of isotactic polypropylene was studied. A change in the phase composition of the film-forming composition during short-term heating during marking was established. The absence of heat shrinkage and change in transparency in non-polarized light was shown, which provides the possibility of hidden recording of information and its contrast manifestation in a passing light stream at a certain arrangement of light filters.Conclusions. The causes and optimal conditions of the thermochromic effect are established. It is proposed to use local contact heat treatment of a polypropylene film for covert recording of information and marking of product packaging in order to protect against counterfeiting.